Gene annotation of Linum trigynum - Fracassetti, Marco; Slotte, Tanja; Gutierrez-Valencia, Juanita; Zervakis, Panagiotis-Ioannis; Postel, Zoé; Bunikis, Ignas; Soler, Lucile; Losvik, Aleksandra; Desamore, Aurelie; Hughes, P. William; Mehrabi, Sara; Laenen, Benjamin; et al. (Stockholm University, 2024)
The file contains the genes annotation of Linum trigynum genome.

The genome has been deposited to [ENA](https://www.ebi.ac.uk/ena/browser/home) with the accession id: GCA_964030455 (project PRJEB67577).

The genes annotation has been done with [TSEBRA](https://github.com/Gaius-Augustus/TSEBRA). The genes contained in the S-locus region has been manually annotated using [StringTie](https://ccb.jhu.edu/software/stringtie/) and [TransDecoder](https://github.com/TransDecoder/). The conversion from gtf to gff3 has been done with [AGAT](https://agat.readthedocs.io/en/latest/index.html).

It is part of this article: Gutiérrez-Valencia, J., Zervakis, P. I., Postel, Z., Fracassetti, M., Losvik, A., Mehrabi, S., ... & Slotte, T. (2024). Genetic causes and genomic consequences of breakdown of distyly in Linum trigynum. Molecular Biology and Evolution, msae087. https://doi.org/10.1093/molbev/msae087
Keywords: Evolutionary ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi